FREQUENCY CHARACTERISTICS OF IN CYLINDER PRESSURE OF A GASOLINE ENGINE - Narayan, Sunny (Journal of Applied Engineering Science, 2020)
This presented work analysis of effects of changes in various injection parameters on development of combustion pressure development and noise emissions from engines. Scope of using non-intrusive diagnosis technique has been analyzed by using changing various locations of microphone around the engine. In particular the noise emissions from engines were found to be dependent on quantity of fuel injected inside cylinder. Various characteristic frequency ranges of contributing sources have been identified. Time–Frequency analysis has shown onset of various events associated with working of engine. Based on the identification of various frequency bands, it is possible to device suitable filters in order to extract more information about combustion and motion based noise which is done in later part of this work. It may be used as an effective tool for condition monitoring of engines in order to gain fuel economy. Suitable structural modifications of engine may be also done in order to improve its performance on various noise and vibration benchmarks.